HRI Online 2022: Leading International Experts Illustrate the Positive Impact of Increased Collaboration in Homeopathy Research - Roberts, E. Rachel; Eizayaga, José E.; van der Werf, Esther T.; Tournier, Alexander L. (Homeopathy, 2022)
The Homeopathy Research Institute (HRI) welcomed more than 450 people from 35 countries to their first online event on June 25, 2022. The one-day programme featured an excellent line-up of international speakers and provided a unique interactive platform in keeping with the theme of the event – Key Collaborations in Homeopathy Research. Scientists from a range of different research fields gave an exceptional insight into the current status of homeopathy research. Here we give an overview of the most significant findings in both clinical and basic research presented during HRI Online 2022.
Keywords: homeopathy research; conference; HRI; clinical trials; fundamental research